Pengaruh Corporate Social Responsibility dan Green Accounting terhadap Profitabilitas dengan Citra Perusahaan sebagai Variabel Moderasi. - Chindy Flawdia Putri indy; Nurhayati Siregar; Mutiara Rizqi Nur Rachmi; Josmar Munthe; Sherly Metta Puena (SPT. haria Journal and Education Center Publishing, 2026)
The purpose of this study is to analysis the effect of Corporate Social Responsibility (CSR) and Green Accounting on profitability, using corporate image as a moderating variable in mining companies listed on the Indonesia Stock Exchange from 2021 to 2024. This study is based on the increasing demand for sustainable business practices and environmental accountability in the mining sector. The quantitative method employed in this study is panel data regression. The research sample consists of 26 mining companies, with a total of 104 observations selected using purposive sampling. Green Accounting is measured using the Green Accounting disclosure index, CSR is measured using the CSR index, corporate image is measured using the corporate image index, and profitability is measured by Return on Assets (ROA). Eviews software is used to process the data in this study. The results indicate that Green Accounting and CSR have a positive and significant effect on profitability. However, corporate image is unable to moderate the effect of CSR and Green Accounting on profitability. These findings indicate that environmental and social practices directly influence financial performance, although corporate image has not strengthened or weakened this relationship Keywords: : Corporate Social Reponsibility ,Green Accounting, , Profitability, Corporate Iimage, Mining